2018
DOI: 10.4088/pcc.18m02286
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy for Catatonia With Deep Venous Thrombosis

Abstract: These results suggest that it is important to determine the location of a DVT and to continue anticoagulation therapy until a proximal DVT disappears before ECT is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…In an analysis 9 of 8 patients receiving concomitant ECT and either edoxaban or apixaban for an acute DVT, 1 patient (12.5%) developed a PE during ECT. Reassuringly, other case reports 5,[10][11][12] have indicated that ECT sessions could be completed successfully and without complications after the development of a VTE. One published case report 5 even described safe resumption of ECT as soon as 3 days after heparin initiation for acute PE.…”
Section: Introductionmentioning
confidence: 87%
“…In an analysis 9 of 8 patients receiving concomitant ECT and either edoxaban or apixaban for an acute DVT, 1 patient (12.5%) developed a PE during ECT. Reassuringly, other case reports 5,[10][11][12] have indicated that ECT sessions could be completed successfully and without complications after the development of a VTE. One published case report 5 even described safe resumption of ECT as soon as 3 days after heparin initiation for acute PE.…”
Section: Introductionmentioning
confidence: 87%
“…22 Thromboembolic disease/atrial fibrillation (AF): Risk of pulmonary embolism exists, so location of deep venous thrombosis (DVT) should be determined, and anticoagulation should be continued. 23 Increasing the dose of neuromuscular relaxant is advised. Rate control and anticoagulation are advised for patients in AF to prevent embolic stroke.…”
Section: Specific Cardiac Pathologiesmentioning
confidence: 99%
“…There have been incidences described in the literature where catatonic patients developed deep venous thrombosis and anticoagulation treatment was given to all of them before and during ECT sessions and, consequently, no bleeding-related complications were noted. Literature also suggests that the location of deep venous thrombosis might prove to be an important consideration in these patients as catatonic patients with proximal deep venous thrombosis are more likely to develop pulmonary embolism as a complication as compared to catatonic patients with distal deep venous thrombosis [9]. All of these catatonic patients were given muscle relaxants before the ECT session, so it could not be confirmed whether ECT was directly responsible for pulmonary embolism in one of the patients or other additional factors [9][10][11][12].…”
Section: Figure 1: Flowsheet Describing the Occurrence Of Thromboembomentioning
confidence: 99%
“…Literature also suggests that the location of deep venous thrombosis might prove to be an important consideration in these patients as catatonic patients with proximal deep venous thrombosis are more likely to develop pulmonary embolism as a complication as compared to catatonic patients with distal deep venous thrombosis [9]. All of these catatonic patients were given muscle relaxants before the ECT session, so it could not be confirmed whether ECT was directly responsible for pulmonary embolism in one of the patients or other additional factors [9][10][11][12]. Another literature review highlights three important points that ECT can be administered safely in the psychiatric patient with catatonia after the occurrence of pulmonary embolism, that is, by evaluation of cardiac function and residual deep venous thrombosis before resuming ECT therapy, adjustment of anticoagulation dose and by adopting preventive measures for recurrent deep venous thrombosis and pulmonary embolism like fluid administration, compression devices and timely ECT [13].…”
Section: Figure 1: Flowsheet Describing the Occurrence Of Thromboembomentioning
confidence: 99%
See 1 more Smart Citation